The Proximity of Us-Indian Interest in Afghanistan and Its Implication on Pakistan - Shireen Mushtaq (Journal of Political Studies, 2018)
Afghanistan has been a stage of great power politics for centuries. The US aims in Afghanistan since 2001 has been to counter terrorism, a strategy that has seen several highs and lows, with each President having followed somewhat the same approach with a new title. This protracted conflict has become a burden on the USA economy as she played a major role in the reconstruction and development of Afghanistan along with the constant military presence in Afghanistan. Recently, USA’s President Trump, with his new Afghan Policy has welcomed the Indian involvement in Afghanistan for state building, reconstruction and development, acknowledging that India and USA should work together. At the same time President Trump has denied Pakistan the credit she deserves for facing the brunt of the Afghan conflict that has been raging on to 17 years. Pakistan has been involved in “doing more” in the case of Afghanistan however the acknowledgement for that has been far and few. The relations of US and Pakistan have suffered as a result of this. Now as the Indian strategic and economic interests are aligned with those of USA, the Indian involvement is favored. The proximity of US – Indian interests has several implications on Pakistan that are both strategic and economic in nature. The threat of Indian influence in Afghanistan is not imaginary for Pakistan, this enmity is deep rooted and guided by suspicion. It is therefore becoming a major challenge for Pakistan to pursue her own interests in Afghanistan and the region. Pakistan requires Afghanistan to be a friendly neighbor so that the changing economic regional dynamics and the ensuing economic prosperity as a result of CPEC, can be enjoyed equally by all regional states. However, given the Indian role in Afghanistan and the US policy towards Pakistan, cooperation seems far fetched.